Photographing in the art museum: visitor attitudes and motivations - Stylianou-Lambert, Theopisti (My University, 2017)
There is an animated debate in popular media about whether or not photography should be allowed in art museums. However, there is limited research that examines how visitors themselves feel about visitor photography and the reasons why they choose to take (or not take) photographs in museums. This research, conducted at the Smithsonian National Portrait Gallery in Washington, DC, uses semistructured, in-depth interviews and photo elicitation with 40 adults to examine visitors' attitudes to using photography inside art museums and their motivations for doing so. The research results suggest that visitors with positive attitudes towards visitor photography see photographic devices as tools that enhance certain aspects of the museum experience, promote further education, and provide entry points to exhibitions and a more interactive, personal experience. Those with negative attitudes see photographic devices as mediating and distracting lenses that have a detrimental effect on intimate experiences with artworks. Many of the participants with negative attitudes still use photographic devices because they believe that the risk of diminishing art experiences in the museum is worth taking, considering the potential uses of photography. The six main motivations for taking photographs in museums are (a) to aid memory, (b) to share, (c) for further research, (d) to inspire, (e) as building material for self-identity, and (f) as an art form in its own right.
Keywords: Art museums; Visitors; Photographic devices